Modulation of PD‑L1 expression by standard therapy in head and neck cancer cell lines and exosomes - Affolter, Annette; Liebel, Kai; Tengler, Luisa; Seiz, Elena; Tiedtke, Moritz; Azhakesan, Alexya; Schütz, Julia; Theodoraki, Marie-Nicole; Kern, Johann; Ruder, Arne Mathias; Fleckenstein, Jens; Weis, Cleo-Aron Thias; et al. (International journal of oncology, 2023)
Although checkpoint inhibitors (CPI) have recently extended the treatment options and improved clinical response of advanced stage head and neck squamous cell carcinoma (HNSCC), treatment success remains unpredictable. Programmed cell death ligand‑1 (PD‑L1) is a key player in immunotherapy. Tumor cells, and exosomes derived therefrom, are carriers of PD‑L1 and efficiently suppress immune responses. The aim of the present study was to analyze the influence of established therapies on PD‑L1 expression of HNSCC cell lines and their exosomes. The HNSCC cell lines, UM‑SCC‑11B, UM‑SCC‑14C and UM‑SCC‑22C were treated with fractionated radiotherapy (RT; 5x2 Gy), cisplatin (CT) and cetuximab (Cetux) as monotherapy, or combined therapy, chemoradiotherapy (CRT; RT and CT) or radioimmunotherapy (RT and Cetux). The expression of PD‑L1 and phosphorylated (p)ERK1/2 as a mediator of radioresistance were assessed using western blotting, immunohistochemistry and an ex vivo vital tissue culture model. Additionally, exosomes were isolated from concentrated supernatants of the (un‑)treated HNSCC cell lines by size exclusion chromatography. Exosomal protein expression levels of PD‑L1 were detected using western blotting and semi‑quantitative levels were calculated. The functional impact of exosomes from the (un‑)treated HNSCC cell lines on the proliferation (MTS assay) and apoptosis (Caspase 3/7 assay) of the untreated HNSCC cell lines were measured and compared. The HNSCC cell lines UM‑SCC‑11B and UM‑SCC‑22B showed strong expression of pERK1/2 and PD‑L1, respectively. RT upregulated the PD‑L1 expression in UM‑SCC‑11B and UM‑SCC‑14C and in exosomes from all three cell lines. CT alone induced PD‑L1 expression in all cell lines. CRT induced the expression of PD‑L1 in all HNSCC cell lines and exosomes from UM‑SCC‑14C and UM‑SCC‑22B. The data indicated a potential co‑regulation of PD‑L1 and activated ERK1/2, most evident in UM‑SCC‑14C. Exosomes from irradiated UM‑SCC‑14C cells protected the unirradiated cells from apoptosis by Caspase 3/7 downregulation. The present study suggested a tumor cell‑mediated regulation of PD‑L1 upon platinum‑based CRT in HNSCC and in exosomes. A co‑regulation of PD‑L1 and MAPK signaling response was hypothesized.